Metabolic Effects of D-Chiro-Inositol and Myo-Inositol in Polycystic Ovary Syndrome - Rim Hanna; Tarek Wehbe; Elizabeth Abou Jaoude (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2017)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age.  The  pathogenesis  has  not  been  fully  deciphered.  PCOS  is  associated  with  insulin  resistance  (IR), menstrual irregularities, cardiovascular disease, obesity, hirsutism, infertility, and endometrial cancer. The use  of  D-chiro-inositol  (DCI)  for  the  treatment  of  IR  in  PCOS  has  been  controversial  with  contradictory data being published. Our objective is to evaluate the effect of DCI combined with myo-inositol (MI), and metformin on the metabolic outcomes of PCOS in a Lebanese women cohort. This is a prospective study of 150 Lebanese women diagnosed with PCOS and treated with Ovacure® (DCI+MI+folic  acid),  or  a  combination  of  Ovacure®  and  metformin.  Patients  aged  13  to  55  years  were randomly  selected  from  different  clinics  in  Beirut  and  Mount  Lebanon.  A  questionnaire  covering  the personal  and  health  status,  physical  activity,  medications  and  anthropometrics  was  completed  before enrolment. The prevalence of obesity in our population was 35.3%. Although IR was more prevalent among obese women  with  PCOS,  non-obese  subjects  were  also  found  to  have  a  significant  incidence  of  IR.  After  a  6 months course of treatment with Ovacure®, a significant decrease in fasting glucose, HOMA-IR, Glycated Hemoglobin  (HbA1c),  Low  Density  Lipoprotein  (LDL),  Triglycerides  (TG),  weight  and  Body  mass  index (BMI)  levels  were  noted.  Furthermore,  adding  metformin  to  Ovacure®,  lowered  weight  and  BMI  further but not IR. In this study, we show that the combination of MI and DCI may improve the metabolic profile in PCOS.The addition of metformin may help control overweight further but not IR.